Efficacy and Safety of Ultrasound-Guided Sciatic Nerve Block as Primary Anesthesia for Diabetic Foot Surgery in Libyan patients - Fathi Abulifa; Ibrahim Garta; Ahmed Aniba; Omar Danfour; Mona Abujazia (AlQalam Journal of Medical and Applied Sciences, 2026)
Diabetic foot syndrome frequently necessitates surgical intervention in patients with significant cardiovascular and metabolic comorbidities. Both general anesthesia and central neuraxial techniques carry inherent risks of hemodynamic instability in this vulnerable population. Although ultrasound-guided sciatic nerve blocks represent a promising regional alternative, their efficacy and safety profile have not been thoroughly characterized in Libyan diabetic patients. We conducted a retrospective cohort analysis of 70 consecutive adults (42 males and 28 females) who underwent elective unilateral diabetic foot surgery with ultrasound-guided sciatic nerve block as the primary anesthetic at Misurata Medical Center in Libya between January 2023 and December 2024. Primary endpoints included block success rate and intraoperative hemodynamic stability, assessed through maximum absolute fluctuations in systolic blood pressure and heart rate from baseline, measured at 5-minute intervals during the operative period. Secondary outcomes included patient satisfaction and adverse events. The procedure achieved an 87.1% success rate (61 of 70 patients). Successful blocks demonstrated significantly superior hemodynamic stability. Mean maximum systolic blood pressure fluctuation was substantially lower in the success group (8.6± 3.5 mmHg) than in the failure group (19.4±6.9 mmHg), with a mean difference of 10.8 mmHg (95% CI [7.2, 14.4]; p < 0.001). Heart rate fluctuation was markedly attenuated in successful blocks (4.2±1.8 bpm versus 13.6±4.7 bpm; p < 0.001). The incidence of severe hypertensive episodes (systolic blood pressure >180 mmHg) was substantially lower in the success group (6.6% versus 55.6%; p < 0.001). Patient satisfaction scores were significantly higher in successful blocks (8.6 ± 1.4 versus 3.3 ± 1.4; p < 0.001). Adverse events included transient paresthesia (4.3%), hematoma formation (0.6%), and minor vascular injury (1.2%), with no major complications recorded. Ultrasound-guided sciatic nerve block represents an effective and safe primary anesthetic modality for diabetic foot surgery in both male and female patients. The combination of favorable success rates, superior hemodynamic stability, and minimal complications positions it as a preferred option for this high-risk population."